2020
DOI: 10.1002/fsn3.1798
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soy fortification on the quality of Mkarango a traditional Kenyan fermented maize meal snack

Abstract: This study aimed at improving the quality and nutrient density of a Kenyan fermented maize meal snack (mkarango) through soy fortification to alleviate protein‐energy malnutrition (PEM) in children. Nine variations of the snack were prepared by replacing 0, 30, and 50% maize with soy and fermenting each for 0, 3, and 5 days at ambient temperature. To establish the physico‐chemical characteristics, the proximate composition, bulk density, water, and oil absorption capacities and titratable acidity were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…Similar findings to this research work have been reported by Rapando et al. ( 2020 ) while working with fermented maize meal snacks fortified with soybean for school feeding programs. Furthermore, Dewi et al.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Similar findings to this research work have been reported by Rapando et al. ( 2020 ) while working with fermented maize meal snacks fortified with soybean for school feeding programs. Furthermore, Dewi et al.…”
Section: Resultssupporting
confidence: 92%
“…The reduction in energy and protein can be attributed to increased requirements for metabolism, growth, and development (Michaelsen et al, 2009). Similar findings to this research work have been reported by Rapando et al (2020) while working with fermented maize meal snacks fortified with soybean for school feeding programs. Furthermore, Dewi et al (2020) found that consumption of one serving size of biscuits fortified with wood grasshopper flour contributed to the adequacy of protein per day by 24%-38% RDA of children aged 12-24 months.…”
Section: Moisturesupporting
confidence: 88%
“…Comparing these results with those obtained in the present work, it is observed that flavored products, such as the snacks analyzed, received higher scores, and hence are better accepted than those that are unflavored. Rapando et al (2020) evaluated consumers' acceptance of three formulations of soy fortified snacks subjected to different fermentation periods and they observed that samples fermented without soy were better appreciated (using nine-point hedonic scale) than the samples that incorporated soy and were subjected to fermentation [22]. As previously mentioned, one of the lines of research that shows high current interest consists of the development of gluten free snack type products, such as the samples analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%